Production of Endoglucanase by Fusarium solani Grown in Solid-State Fermentation - Nawaz Bhatti, Haq; Nawaz, Shah (Asian Journal of Chemistry, 2010)
Corn cob is an abundant lignocellulosic agricultural waste. In this investigation, the production of endoglucanase from this lignocellulosic biomass under solid state fermentation was investigated. The effects of various process parameters, such as initial moisture content, initial culture pH, amount of substrate, incubation period on endoglucanase production by a mesophilic fungus Fusarium solani, were studied. With an initial moisture content of 70 %, a pH of 5.0, maximum endoglucanase activity (312 ± 16 U/gds) was obtained with 15 g of corn cobs after 96 h. Addition of nitrogen sources further enhanced the endoglucanase production.